Dramaturgias e Epistemologias Insurgentes na Dança - Vieira, Marcilio de Souza; Tourinho, Lígia Losada; Rocha, Lucas Valentim; Souza, Marco Aurélio da Cruz (ARJ – Art Research Journal: Revista de Pesquisa em Artes, 2022)
Editorial para ARJ, v. 9, n. 2, 2022. Apresenta o dossiê especial e demais artigos.